Industrial training report: Columbia Asia Hospital - Seremban - Mohd Ramlan, Balqis Auni (Faculty of Business and Management, 2025)
This report was written as an internship report during my industrial training at Columbia Asia - Seremban for 24 weeks. It is a part of the Bachelor Business Administration (Hons.) Marketing programme at UiTM which is subject MGT666 also known as industrial training for the student to experience and learn the daily workplace. I have completed my internship for 24 weeks at Columbia Asia Hospital - Seremban from 12 August 2024 until 24 January 2024 which is equivalent to six-months. The purpose of this internship report is to analyse the strengths, weaknesses, opportunities and threats also known as SWOT Analysis of Columbia Asia Hospital - Seremban. By doing this, we can identify certain issues and problems in order to improve the company’s business growth and performance in the future. For this report, I use secondary data sources as the references. As for this company, Columbia Asia Hospital - Seremban is one of the prominent healthcare companies in Seremban and they are also known as one of the largest and fastest- growing international private healthcare companies with an extensive network of hospitals across Southeast Asia. During my internship at Columbia Asia - Seremban, I was assigned as a Marketing Assistant for the Marketing Department under my marketing manager Ms. Didi Chan Li Hong. I learned many invaluable lessons about the marketing sector and also in the healthcare industry. As for the SWOT Analysis, Columbia Asia Hospital - Seremban’s strengths are experience and skilled staff, positive workplace environment and established brand. For the weaknesses, limited space, potential burnout due to limited staff and lack of social media presence. For opportunities, an aging population leads to increase in healthcare, technological advancement and expansion of 11 level building. Lastly are threats such as new policies of Bank Negara and increase in competition. Therefore, this report shows the details of Columbia Asia Hospital - Seremban as a whole and also my experience or what I gained during my internship. It was an invaluable lesson of my education for being part of the marketing team in Columbia Asia Hospital.